MODELLING OF RADIO MONITORING SYSTEM OF SHORT-WAVE RADIO COMMUNICATION ADAPTIVE SYSTEMS - B. A. Liakh; V. A. Kondratyonok (Системный анализ и прикладная информатика, 2015)
The structure of model which allows to spend an estimation of system functioning efficiency of radio monitoring system of shortwave radio communication adaptive systems in adverse conditions of influence of external jams is described.